380PVentricular–Subventricular zone involvement: A predictive factor for survival in glioblastoma. (24th November 2019) - Pareek, V; Bhalavat, R; Chandra, M
Abstract: Background: MRI imaging is an essential tool in diagnosing glioblastoma and it can give various anatomical details related to disease. It gives an assessment of involvement of disease with ventricular – subventricular zone (VSVZ), subgranular (SGZ) and corpus callosum (CC). This study aims at assessment of survival outcomes in diseases involving neurogenic zones and corpus callosum and the associated prognostic factors. Methods: We retrospectively analyzed 376 adult patients treated for histologically proven Glioblastoma. MRI studies were assessed for the tumor volume and its association with the neurogenic zones and corpus callosum. Age of patient, comorbidities associated, performance status, extent of resection and radiation doses received by these structures were evaluated. Overall (OS) and progression free (PFS) survivals were calculated and analyzed with multivariate Cox analyses. Results: Of the 376 patients, 121 had VSVZ involved, 62 had CC involved and 43 had SGZ involved and remaining 150 had cortical involvement and the latter served as controls. Overall median age was 60.4 years, median Karnofsky performance score (KPS) was 80 and median tumor volume was 34.7 cm 3 . Gross total resection (GTR) was seen in 50.6% and subtotal resection in 38.1% and rest were unresectable. On multivariate cox analyses, VSVZ was found to be an independent factor for poor OS and PFS. Besides, increasing age, lower KPS, less than GTR status were associated independent factors for reduced survival. Conclusions: Patients with GBMs contacting the VSVZ and SGZ neurogenic zones exhibit divergent clinical patterns of tumor recurrence and survival and VSVZ involvement are associated with early recurrences and lower survival. VSVZ has a rich stem cell and growth factor microenvironment and these structures can be considered as organs at risk in uninvolved disease for probably better outcomes. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.